Take-up and earnings from a livestock financing project in Bangladesh - Ambler, Kate; Bakhtiar, M. Mehrab; de Brauw, Alan; Uddin, Mohammad Riad (CGIAR System Organization, 2024)
Smallholder farmers in low- and middle-income countries often encounter significant challenges in accessing financial services, primarily due to the limited presence of formal financial institutions in rural areas (DemirgüçKunt et al., 2022). These challenges are compounded by factors such as the high costs and risks associated with financing small, dispersed farms and the farmers’ lack of collateral (Barrett et al., 2022; Dorward et al., 2009). Despite the emergence of microfinance as a tool to bridge this gap, the rigid repayment structures required by most microfinance institutions frequently clash with the seasonal nature of agricultural production, creating financial strain for farmers (Armendáriz and Morduch, 2010). These challenges underscore the need for more flexible and tailored financial solutions for smallholder farmers.